The Impact of Information Technology Implementation on Firm Performance: The Mediating Roles of Supply Chain Collaboration, Innovation Capability, and Supply Chain Resilience - Cecilia Antonive Chandra; Zeplin Jiwa Husada Tarigan; Maria Natalia Damayanti Maer (Petra International Journal of Business Studies, 2026)
Information technology is important for companies in producing supply chain collaboration, innovation capability, and supply chain resilience. The company's ability to maintain continuity in information technology implementation can enhance its performance in manufacturing companies in East Java. Data collection was carried out on manufacturing companies in East Java using a survey method, targeting medium- and large-category companies with purposive sampling that have implemented information technology for at least 2 years. Respondents were permanent employees with at least 2 years of experience.  The analysis used is PLS-SEM, which met the goodness-of-fit requirements for the inner and outer models. The study found that implementing information technology positively affects supply chain collaboration, innovation capability, and supply chain resilience. Supply chain collaboration affects innovation capability and firm performance, but not directly supply chain resilience. The results of the study show that innovation capability positively affects supply chain resilience and company performance. The study's results also show that supply chain resilience improves company performance. Overall, the results of the study confirm that implementing integrated information technology strengthens collaboration in the supply chain, enhances innovation capabilities, and builds supply chain resilience, ultimately improving company performance. The results of the research contribute practically by providing insights for the management of companies seeking to sustainably develop information technology investments, strengthen collaboration with partners, and encourage organizational innovation to improve competitiveness and long-term performance.